Correlation of death anxiety with coping strategies among Palestinian women with breast cancer: a cross-sectional study - Ahmead, Muna; Shehadah, Feda; Abuiram, Issa (Frontiers in Public Health, 2024)
Background Death anxiety and maladaptive coping accompany breast cancer diagnoses. The coping mechanisms and death anxiety among Palestinian patients with breast cancer have not been studied. Aim To assess the prevalence of death anxiety and its relationship with coping strategies among Palestinian women with breast cancer who are treated in Beit Jala Governmental Hospital in Bethlehem. Method A cross-sectional design was used, and 214 breast cancer patients who visited the Beit Jala Governmental Hospital in Bethlehem were recruited. Templer's Death Anxiety Scale and the Brief COPE Scale were used. To investigate the relationship between coping strategies and death anxiety, frequency, percentages, chi-square tests, and Pearson's correlation tests were utilized. Results The results indicated that 58.40% of the patients experienced death anxiety. The participants who used positive reframing (adjusted odds ratio (AOR) = 1.487, p = < 0.026), self-blame (AOR = 1.309, p = < 0.023), and religion (AOR = 1.260, p = < 0.031) as coping mechanisms were more likely to experience death anxiety. Conversely, the participants who adopted substance use (AOR = 0.657, p < 0.005) and active coping (AOR = 0.629, p < 0.007) as coping strategies had a lower likelihood of experiencing death anxiety. Conclusion The study revealed that breast cancer patients tended to use a combination of functional and emotional coping strategies and that a significant proportion of these patients (58.4%) experienced symptoms of death anxiety. This study emphasizes the significance of screening for death anxiety and understanding the coping strategies utilized by the patients. Gaining this understanding will assist in identifying patients who need more guidance and support.